La sémantique du prototype et les genres (littéraires) - Wołowski, Witold (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2006)
The proposal of this paper, situated at the meeting point of linguistics and poetics, is to discuss the applicabilty of same selected prototypical thesis to the research on litterary genres. It examines the following questions: status and internal structure of generic categorisations (hierarchical levels, gra-duality), J.-M. Adam's sequential theory, origin of prototypicality judgements in literature, archetype-prototype relation, difficulties in prototypical analysis of generic hybridity
The semantics of prototype and (literary) genres